1991
DOI: 10.1104/pp.96.4.1376
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Jasmonate and Transpiration in Barley

Abstract: Transpirational water loss from barley (Hordeum vulgare L. var

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 8 publications
3
16
1
Order By: Relevance
“…Similar results were obtained in other monocot and dicot species by Ueda et al (1981), Popova et al (1988), Herrmann et al (1989), Maslenkova et al (1990), Parthier (1990), and Koda (1992). Some authors pointed out that the concentrations of JAs used (in the range of 10 −5 to 10 −3 M) might act as a toxic factor (Horton 1991, Tizio 1996.…”
Section: Resultssupporting
confidence: 59%
“…Similar results were obtained in other monocot and dicot species by Ueda et al (1981), Popova et al (1988), Herrmann et al (1989), Maslenkova et al (1990), Parthier (1990), and Koda (1992). Some authors pointed out that the concentrations of JAs used (in the range of 10 −5 to 10 −3 M) might act as a toxic factor (Horton 1991, Tizio 1996.…”
Section: Resultssupporting
confidence: 59%
“…This also agrees with the studies of Hristova and Popova (2002), who observed a decline in the photosynthesis of barley leaves, but it is in contrast to the findings of Suhita et al (2003). The transpiration rate of soybean plants submitted to MJ treatment exhibited slight reduction as reported previously in barley (Horton, 1991). These results suggested that, MJ is the key component for the observed inhibition in drought-stressed soybean plants.…”
Section: Discussionsupporting
confidence: 92%
“…Jasmonate-induced stimulation of stomatal closure has been suggested as an important factor in the senescenceaccelerating activity of these compounds (Satler andThimann 1981, Raghavendra andReddy 1987). However, according to Horton (1991), JA-ME has been effective in stomatal closure only at high concentrations, when a closure could be ascribed to an irreversible toxic effect of the JA-related compounds.…”
Section: 5-biphosphate Carboxylasementioning
confidence: 99%